Hubungan Antara Kecerdasan Emosional Dan Konformitas Kelompok Teman Sebaya Dengan Konsep Diri RemajaHubungan Antara Kecerdasan Emosional Dan Konformitas Kelompok Teman Sebaya Dengan Konsep Diri Remaja - Indrayana, Praditya (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This study examined the correlation between emotional intelligence and peer group conformity to adolescent self-concept. The subjects were the students of class XI students of SMK Taman Siswa Mojokerto. The populationwere 480 students, then 144 students were taken out as the sample of this study. The data collection of this study was got through questionnaire. This study used multiple regression analysis to analyze the data. This study indicated that there is a positive correlation between emotional intelligence and peer group conformity toadolescent self-concept shown by the  value of F = 76.309  with  p = 0.000 (p <0.05). There is also a positive correlation between emotional intelligence and self-concept of adolescents shown by the value of  t = 9.654  withp = 0.000 (p <0.05).  This study showed  no positive correlation between peer group conformity with adolescent self-concept because  the value of  t = 0.601 p = 0.594 (p> 0,05). Keywords: adolescent self-concept, emotional intelligence, peer group conformity